Middle Power Dreaming : Mexico between Aspirations and Reality - Ivanovic, Marija (2016)
This thesis examines the case of Mexico as middle power. More precisely, it tries to see what were the limitations and possibilities that Mexico faced in the period 2000-2012, while trying to engage more in the international system and rise its international profile. The PAN governments that were in power at that time devoted much of their energy trying to better international position of Mexico, and implicitly the thesis will answer the question of how successful were their strategies.